Perception of Store Owners on Marketing of Processed Peanut Products in Central Java - Amron, Amron (Advances in Social Sciences Research Journal, 2018)
The aim of this study was to examine the relationship between the variables of product, promotion, and distribution with buying decisions on processed peanut food products in Central Java, Indonesia. This study was different from previous studies because it viewed at the marketing of processed peanut products from the point of view of shop owners who bought various brands of processed peanut food products for resale to endusers. The results of this study validate the strong relationship of the three independent variables with buying decision. Surprisingly, however, this study found that product variable had greater effect than the other two variables with a higher level of significance. This research suggest to company managements to always improve product quality, promotion, and distribution in their promotion program. However, in the implementation, corporate managements should pay greater attention to product quality. It is in line with the findings of the research that product variable has a greater effect compared with promotion and distribution variables.